BLENDED LEARNING IN HIGHER EDUCATION - Ramírez Cano, Martha Guadalupe (Atenas, 2015)
In the present investigation the inclusion of blended learning modality (blended learning) in higher education as an alternative to respond to the great challenges of the XXI century facing university teaching, innovation in practice and the impact of expressed Information Technology and Communication in education. This model allows potentiate learning college students because integrates and virtual mode resorting to the use of ICT, which have transformed the way of learning and access to knowledge.